From Crisis to Diagnosis: A Case of Hypertriglyceridemic Pancreatitis as the First Clinical Presentation of Type 1 Diabetes - Subashini Vadivel; Sheetal Nandha Kishore; Jagannath S Dhadwad; Janvi Panchal (Journal of Clinical and Diagnostic Research)
Acute Pancreatitis (AP) is a prevalent and rapidly progressive inflammatory disorder of the pancreas, often presenting with abdominal pain and elevated serum pancreatic enzymes. The present case report emphasises the crucial need for accurately diagnosing the underlying cause of Hypertriglyceridemic Pancreatitis (HTGP) in patients who present without any pre-existing co-morbidities. A 16-year-old female presented with a three-day history of generalised abdominal pain, vomiting and low-grade fever, with no co-morbidities. Initial clinical assessment revealed signs of dehydration, tachypnoea, tachycardia and diffuse abdominal tenderness. Laboratory workups indicated a significant rise in amylase and lipase, hyperglycaemia, metabolic acidosis and pronounced Hypertriglyceridemia (HTG). Imaging studies corroborated the diagnosis of AP, revealing necrotic fluid collections. The patient was immediately started on plasmapheresis, aggressive intravenous fluid resuscitation, insulin infusion and supportive care, which included electrolyte correction, pain management and vigilant monitoring of vital signs. The autoantibody panel for type 1 diabetes, Antiglutamic Acid Decarboxylase antibodies (GAD) returned positive. Over the following days, the patient exhibited marked clinical improvement, with decreased abdominal tenderness, stabilisation of vital parameters and normalisation of biochemical abnormalities. Subsequent imaging confirmed the resolution of pancreatitis. Upon discharge, the patient was prescribed a regimen of insulin, statins, fenofibrate and saroglitazar for ongoing management of her lipid levels and diabetes. This case underscores that HTG may present as the first clinical manifestation of Type 1 Diabetes Mellitus. It also emphasises the critical importance of prompt and coordinated therapeutic interventions in managing HTGP, where early and effective treatment is crucial for optimising patient outcomes.